Aberrant GATA2 Activation in Pediatric B-Cell Acute Lymphoblastic Leukemia - Wang, Han; Cui, Bowen; Sun, Huiying; Zhang, Fang; Rao, Jianan; Wang, Ronghua; Zhao, Shuang; Shen, Shuhong; Liu, Yu (Frontiers in Pediatrics, 2022)
GATA2 is a transcription factor that is critical for the generation and survival of hematopoietic stem cells (HSCs). It also plays an important role in the regulation of myeloid differentiation. Accordingly, GATA2 expression is restricted to HSCs and hematopoietic progenitors as well as early erythroid cells and megakaryocytic cells. Here we identified aberrant GATA2 expression in B-cell acute lymphoblastic leukemia (B-ALL) by analyzing transcriptome sequencing data obtained from St. Jude Cloud. Differentially expressed genes upon GATA2 activation showed significantly myeloid-like transcription signature. Further analysis identified several tumor-associated genes as targets of GATA2 activation including BAG3 and EPOR. In addition, the correlation between KMT2A-USP2 fusion and GATA2 activation not only indicates a potential trans-activating mechanism of GATA2 but also suggests that GATA2 is a target of KMT2A-USP2. Furthermore, by integrating whole-genome and transcriptome sequencing data, we showed that GATA2 is also cis activated. A somatic focal deletion located in the GATA2 neighborhood that disrupts the boundaries of topologically associating domains was identified in one B-ALL patient with GATA2 activation. These evidences support the hypothesis that GATA2 could be involved in leukemogenesis of B-ALL and can be transcriptionally activated through multiple mechanisms. The findings of aberrant activation of GATA2 and its molecular function extend our understanding of transcriptional factor dysregulation in B-ALL.